Crystal structure and spectral studies of green fluorescent protein (GFP) chromophore analogue ethyl 2-[(4Z)-(6-hydroxy naphthalen-2-yl) methylene)-2-methyl-5-oxo-4,5-di hydro-1H-imidazol-1-yl] acetate - Puthuvakkal, Anisha; Manoj, Kochunnoonny (European Journal of Chemistry, 2019)
Synthetically modified green fluorescent protein chromophore derivative was prepared, its crystal structure and spectral properties were studied. Crystal data for C19H18N2O4: triclinic, space group P-1 (no. 2), a = 8.2506(17) Å, b = 11.934(2) Å, c = 17.461(4) Å, α = 102.89(3)°, β = 94.62(3)°, γ = 96.68(3)°, V = 1654.5(6) Å3, Z = 4, T = 173(2) K, μ(MoKα) = 0.096 mm-1, Dcalc = 1.358 g/cm3, 7227 reflections measured (4.722° ≤ 2Θ ≤ 53.996°), 7227 unique (Rint = 0.0453, Rsigma = 0.0662) which were used in all calculations. The final R1 was 0.0561 (I > 2σ(I)) and wR2 was 0.1658 (all data). The single crystal structure showed, the benzylidine moiety adopts Z-conformation in solid state and the molecules were associated by various O−H···O and C−H···O non-covalent interactions. The UV absorption-emission spectral analysis indicated that a significant red shift of emission observed at alkaline pH indicating its utility for live cell imaging applications.